Clinical Care Providers' Perspectives on Body Size and Weight Management Among Long-Term Cancer Survivors. (May 2015) - Baker, Allison M.; Smith, Katherine C.; Coa, Kisha I.; Helzlsouer, Kathy J.; Caulfield, Laura E.; Peairs, Kimberly S.; Shockney, Lillie D.; Klassen, Ann C.
Objective . To examine clinical care providers' perspectives on cancer survivors' body size and weight management. Study Design . In-depth, semi-structured, qualitative interviews. Methods . Interviews were conducted with 33 providers (eg. oncologists, surgeons, primary care providers, nurses, dietitians) across academic and community clinical settings. They were transcribed, coded, and analyzed thematically using constant comparative analysis. Results . Providers conceptualized weight in relation to acute treatment, cancer outcomes, or overall health/comorbidities. These patterns were reflected in their reported framing of weight discussions, although providers indicated that they counsel patients on weight to varying extents. Perspectives differed based on professional roles and patient populations. Providers reported that survivors are motivated to lose weight, particularly due to comorbidity concerns, but face numerous barriers to doing so. Conclusion . Providers described survivor-level and capacity-level factors influencing survivors' weight management. Differences by provider type highlighted the role of provider knowledge, attitudes, and beliefs in clinical encounters. Opportunities for research and intervention include developing and disseminating evidence-based clinical resources for weight management among cancer survivors, addressing capacity barriers, and exploring communication strategies at interpersonal and population levels.